2022
DOI: 10.1159/000521809
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of a Novel Transcutaneous PCO<sub>2</sub> and PO<sub>2</sub> Sensor with Optical PO<sub>2</sub> Measurement in Neonatal Intensive Care: A Single-Centre Prospective Clinical Trial

Abstract: <b><i>Background and Objectives:</i></b> Transcutaneous PCO<sub>2</sub> and PO<sub>2</sub> measurement systems offer non-invasive blood gas trend monitoring. The aim of this prospective study was to assess bias and precision of a transcutaneous PCO<sub>2</sub> and PO<sub>2</sub> measurement system incorporating a novel pO<sub>2</sub> sensor (Sentec OxiVenT™) in neonates ≥34 weeks of gestational age (GA) admitted to intensive ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…Other studies found that the sampling method or mode of ventilation could affect the accuracy of TcCO 2 measurements. For example, Mukhopadhyay et al found that HFOV support significantly increases the odds of increased bias [20], and others found that tcCO 2 was more accurate for capillary blood samples than for arterial blood samples [16,20,27]. In our study, 84% of the samples were within an absolute range of ±10 mmHg.…”
Section: Discussionsupporting
confidence: 43%
“…Other studies found that the sampling method or mode of ventilation could affect the accuracy of TcCO 2 measurements. For example, Mukhopadhyay et al found that HFOV support significantly increases the odds of increased bias [20], and others found that tcCO 2 was more accurate for capillary blood samples than for arterial blood samples [16,20,27]. In our study, 84% of the samples were within an absolute range of ±10 mmHg.…”
Section: Discussionsupporting
confidence: 43%
“…Respiratory failure can cause decreased tidal volume and Functional Residual Capacity (FRC) and requires respiratory assistance. Chest X-Ray, respiratory function monitors, transcutaneous blood gas monitoring, capnography and blood gas analysis are the most used tools to understand the evolution of the respiratory picture of new-borns at NICU [15,16]. In studies and in clinical practice, monitoring of respiratory function in new-borns admitted in the neonatal intensive care units uses various radiation-free imaging technologies [15,17], including lung ultrasound [2,18], electrical impedance tomography (EIT) [19][20][21][22], and segmentography (EIS) [5].…”
Section: Discussionmentioning
confidence: 99%
“…The accuracy of these algorithms may vary depending on the patient physiology, the device used, and the environment. [13] The accuracy of the transcutaneous non-invasive measurements can be affected by several factors including skin perfusion, skin condition, patient movement, temperature, environmental factors, and potentially other health conditions of the patient [6,14,15]. Since these devices rely on the diffusion of oxygen and carbon dioxide through the skin, poor skin perfusion will not allow accurate measurements [16].…”
Section: Introductionmentioning
confidence: 99%